SYSTEM OF BUYING SEEDS AND GOODS FOR OIL PALM PLANTATIONS ON PT GEMAREKSA MEKARSARI - Sri Handayani; Sahni Damerianta Purba, SKom, MMSI (Jurnal Sistem Informasi, 2001)
With the computerized system is expected that the existing system of purchase and after the computer's manual will be faster to handle the purchase of data access. These companies can work well, it is necessary vital information such as order data, the number of orders, all of which was to support the process of the company. With the design that are necessary for activities in the company "PT Gemareksa Mekarsari" The impact it would have looked good at this now includes making goods orders data is then stored in a computer, order the goods there in the message file so that the required items can be fulfilled by warehouse section purchasing department.